Cerebrospinal Fluid Hypovolemia and Posterior Reversible Encephalopathy Syndrome - Zheng, Yuan-yuan; Weng, Xiong-peng; Fu, Fang-wang; Cao, Yun-gang; Li, Yan; Zheng, Guo-qing; Chen, Wei (Frontiers in Neurology, 2020)
Posterior reversible encephalopathy syndrome (PRES) is a reversible neuroradiological syndrome characterized by reversible vasogenic edema. The pathophysiological mechanism is still unclear, but PRES may be triggered by various etiologies. To date, only a few PRES cases linked to cerebrospinal fluid (CSF) hypovolemia were reported. The association between PRES and CSF hypovolemia needs to be explored. We presented a case of PRES with CSF hypovolemia as a result of an inadvertent dural puncture and reviewed the literature to identify the clinical characterization and pathophysiological mechanism of PRES following CSF hypovolemia. A total of 31 cases of PRES-CSF hypovolemia was included for analysis. The median age was 33 years, with a notable female predominance (87.1%). Fifteen patients (48.4%) didn't have either a history of hypertension nor an episode of hypertension. The most common cause of CSF hypovolemia was epidural or lumbar puncture (n = 21), followed by CSF shunt (n = 6). The median interval between the procedure leading to CSF hypovolemia and PRES was 4 days. Seizure, altered mental state, and headache were the most frequent presenting symptom. The parietooccipital pattern was most frequent (71.0%). Conservative management remains the mainstay of treatment with excellent outcomes. Three patients had a second episode of PRES. CSF hypovolemia is a plausible cause of PRES via a unique pathophysiologic mechanism including arterial hyperperfusion and venous dysfunction. Patients with CSF hypovolemia is more susceptible to PRES, which is potentially life-threatening. Given that CSF hypovolemia is a common complication of anesthetic, neurological, and neurosurgical procedures, PRES should be early considered for prompt diagnosis and appropriate management.